The Critique of the Price Specie Flow: A Historical Note - Stefan Homburg (Ordo: Jahrbuch für die Ordnung von Wirtschaft und Gesellschaft, 1990)
The article reminds of two seminal contributions by Fritz Walter Meyer and Paul Anthony Samuelson who showed that Hume's price specie flow is logically incorrect. – – Der Artikel erinnert an zwei wertvolle Beiträge von Fritz Walter Meyer und Paul Anthony Samuelson, die beide zeigten, daß Hume's Geldmengen-Preis-Mechanismus logisch fehlerhaft ist.
Keywords: F32; F41; 330; Price specie flow; Geldmengen-Preis-Mechanismus